Revolutionary Marketing Strategy: Optimising Social Media Utilisation as an Effective Tool for MSMEs in the Digital Age - Ohara, Muammar Revnu; Suparwata, Dewa Oka; Rijal, Syamsu (PT. LITERASI SAINS NUSANTARA, 2024)
The development of information technology, especially in the field of social media, has created a new paradigm in the business world. Micro, Small, and Medium Enterprises (MSMEs) as the backbone of the national economy, need to adapt to these changes to be able to compete in an increasingly complex digital era. This research aims to identify revolutionary marketing strategies that can help MSMEs optimise the utilisation of social media as an effective tool in facing the challenges of the digital era. This research method is a descriptive qualitative literature review that uses primary data sources from scholarly articles found through Google Scholar. This research will conduct an in-depth analysis of relevant and current literature that has been published in the 2021-2023 timeframe. The study results show that revolutionary marketing strategies through optimising the use of social media have proven to be a solid foundation for the success of Micro, Small and Medium Enterprises (MSMEs) in the digital era. Through this approach, MSMEs can build stronger relationships with customers, increase brand visibility, and expand market share. By understanding the target audience, creating creative content, utilising innovative features, and building online communities, MSMEs can transform into key players in a rapidly changing market.